Maximizing Company Value: Unveiling the Impact of Capital Structure and Size, with Profitability as the Key Player - Sholihin, Ahmad -; Hermuningsih, Sri -; Kusumawardhani, Ratih -; Lada, Suddin - (Politeknik Negeri Semarang, 2024)
The purpose of this study is to examine the Effect of Capital Structure and Company Size on Company Value with Profitability as an Intervening Variable. The population of this study consists of companies in the food and beverage industry sector listed on the Indonesia Stock Exchange from 2018 to 2022. The data collection method used is purposive sampling. The information used was lower to be collected using the literature research method. The study was conducted on 51 companies. The data analysis technique uses the multiple linear regression method with the application of SPSS and the Sobel test. Capital structure has a positive influence on profitability, whereas company size does not affect profitability. Capital structure affects the value of the company, while the size and profitability of the company do not affect the value of the company. Furthermore, profitability cannot mediate the relationship between capital structure and firm value, and profitability cannot mediate the relationship between firm size and firm value. Overall, these findings may encourage further revision and development in financial management theory, especially in terms of how firms should prioritize and manage factors such as capital structure and size to achieve their goals. More research may need to be done to explore the specific conditions that influence these associations.